Development of a Mobile Game Application to Boost Students' Motivation in Learning English Vocabulary - Elaish M.M.; Ghani N.A.; Shuib L.; Al-Haiqi A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Mobile computing; Motivation; Students; Education systems; English languages; English-as-a-Foreign-Language; ESL learners; Experimental groups; Mobile applications; Persuasive technology; Teaching English as a foreign languages; Learning systems